2000
DOI: 10.1177/107755870005700103
|View full text |Cite
|
Sign up to set email alerts
|

Does System Membership Enhance Financial Performance in Hospitals?

Abstract: While hospitals continue to join multi-institutional systems, empirical data on the benefits of system membership are ambiguous. This study examines the same 166 Florida hospitals in 1986 and 1992. System membership, in general, did not enhance financial returns (measured by operating margin, total margin, and return on assets) for the pooled data or for either year. In fact, a significant negative relationship is noted in 1986. However, when only hospitals affiliated with national systems (in this study, Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…To gain a better understanding of the overall extent to which the covariates explain variation in operating margins, we also estimated a random-effects operating margin model with the same regressors (results not shown). The random effects ''between'' R-squared was .19, which is consistent with crosssectional studies of hospital margins (Tennyson and Fottler 2000;Younis and Forgione 2005).…”
Section: Resultssupporting
confidence: 80%
“…To gain a better understanding of the overall extent to which the covariates explain variation in operating margins, we also estimated a random-effects operating margin model with the same regressors (results not shown). The random effects ''between'' R-squared was .19, which is consistent with crosssectional studies of hospital margins (Tennyson and Fottler 2000;Younis and Forgione 2005).…”
Section: Resultssupporting
confidence: 80%
“…This is consistent with Clement et al (1997), who found that the hospitals' cash flow was not influenced by membership in a strategic hospital alliance. However, our finding regarding hospital profitability is in line with the theoretical framework and consistent with previous studies (Bazzoli et al, 2000;Tennyson & Fottler, 2000). Effective relationships between hospitals and outpatient physicians may not only make sense from a medical point of view, but could also enable hospitals to operate more profitably.…”
Section: The Service Industries Journalsupporting
confidence: 92%
“…We focused on four domains of financial performance that have been identified to explain most of the variance in overall hospital performance: profitability, liquidity, capital structure, and asset efficiency (Das, 2009;Pink, Daniel, McGillis Hall, & McKillop, 2007). These domains have also been analyzed in previous studies (Bazzoli et al, 2000;Tennyson & Fottler, 2000). For each of these domains, we chose one common indicator which will be described in the following (Preißler, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Her application to 1990 American Hospital Association (AHA) data made a methodological contribution in its simultaneous determination of costs and system membership, thus controlling for potential selection bias. Tennyson and Fottler (2000) also found some evidence for improved financial performance for Florida hospitals that were members of national systems. Unlike the majority of previous researchers, these authors used a longitudinal design in reaching their conclusions.…”
Section: Introductionmentioning
confidence: 91%